Effects of upper-limb aerobic exercise plus general exercise versus general exercise alone among patients with spinal cord injury in northern Nigeria: A protocol for a randomized controlled trial - Fatima Kachalla Gujba; Sonill Sooknunan Maharaj; Aminu Alhassan Ibrahim (PLoS ONE, 2025)
Introduction Spinal cord injury (SCI) is a devastating injury often associated with immobility, leading to numerous complications, with cardiovascular disorders being among the major causes of mortality. Upper-limb aerobic exercise (ULAE) may help to retrain and regain some of the abilities lost through SCI and minimize secondary complications. The purpose of this study is to determine the effects of ULAE plus general exercise compared to the same general exercise on cardiovascular parameters, functional independence, and quality of life among patients with SCI in northern Nigeria. Method This is a multicenter, assessor-blind, parallel group, randomized controlled superiority trial to be conducted among SCI patients attending three tertiary hospitals in Kano State, northern Nigeria. Participants fulfilling the study criteria will be randomized into either ULAE (arm ergometer and overhead pulley exercises) plus general exercise group or general exercise only group. Both groups will receive their respective interventions three times per week for 8 weeks. The primary outcomes will be rate pressure product (calculated as systolic blood pressure x heart rate) and functional independence. The secondary outcomes will be blood pressure and quality of life. All outcomes will be assessed at baseline, 8 weeks post-intervention, and at 14weeks follow-up. Discussion This study will be the first to determine the effects of ULAE plus general exercise versus general exercise alone among patients with SCI in northern Nigeria. The outcome of this study could provide valuable guidance for rehabilitation professionals in selecting a low-cost and effective intervention for patients with SCI, particularly in resource-constrained settings. Trial registration Pan African Clinical Registry (PACTR202306580460880). Registered on June 12, 2023.